(3eYQaI GdJfaS hGdfHVs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3aUd ai eYQaI GdJfaS hGdfHV Ndb GdbdH heG jfHYK efg ai GdYQhb hGdTF GdPi jSejg GdCWHGA QhMkG s
(3BNQgG (B:s
(3GdLRQ GdHQi GdSjSGdjhS ef GdOH GdLHdi JeJ GdQSGdI GdehShYI ai GdaUhd GdeSJaGOI ai eLdS GdTjN GdQFjS s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B177 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdWHs